Innovative Leader in Higher Education (Laisvalaikio tyrimai, 2018)
Research background. Changing higher education environment, global competition of universities and colleges, need to react to the changes in labour market created new challenges for higher education institutions, that must implement innovations that help to keep their activity effective and improve it. One of the traits of effective leadership is innovative leadership in higher education institution that is especially oriented towards implementing changes in universities and colleges. Challenges for higher education institution in the context of innovations are widely determined in scientific literature. It is important to identify what are the roles of innovative leader in higher education, and to research the level of innovative leadership in Lithuanian higher education institutions. The object of the research is the innovative leader in higher education. Goal of research is identify main roles of innovative leader in higher education and to determine how they manifest at higher education organization “Kauno kolegija”. Methods of research. Methods of analysis and systemising were used performing theoretical literature analysis. Method of questionnaire survey was used to perform an empirical research, that is, to evaluate how roles of innovative leader manifest at higher education institution “Kauno kolegija” (n = 49). Questionnaire was prepared, Cronbach’s Alpha = 0.76. Results and findings. Analysis of theoretical literature revelsthat working with people is an important part of innovative leader’s agenda. Such a leader should use style of transformational leadership (idealized influence, inspirational motivation; intellectual stimulation, individualized consideration). On the other hand, innovative leader should take part in innovation process. He should initiate important innovations that would improve higher education environment (help a university or college to correspond to challenges of our times; implement new methods of activity and education; stimulate meaningful researches; implement innovations that prepare students for international and internal labour market), and also take part in planning and executing innovations. Results of empirical research performed in higher education institution “Kauno kolegija” reveal that innovative leadership is yet not fully implemented in this organization. Abilities of formal leaders to act as innovative leader and work with people as a transformational leader are not sufficient. Leaders in this organization do not take an adequate role starting innovations that would help organization to cope with challenges of our times, management innovation, or innovations helping students to become prepared for international labour market is rather weak. Main conclusions: 1. Innovative leader should play two main roles in higher education organization: working with people using the style of transformation leadership; and working with innovation process, stimulated right innovations corresponding to the challenges in higher education institution’s environment. 2. Abilities of formal leaders in higher education institution “Kauno kolegija” to act as innovative leader and work with people as a transformational leader are not sufficient; role of innovative leaders in implementing innovations that help institution to cope with challenges in the environment is rather weak.Keywords: innovative leader; innovation; higher education; higher education institution